O trabalho escravo no contexto das políticas migratórias : o direito ao desenvolvimento como referencial de enfrentamento - Britto, Christiane Rabelo (2019)
The migratory flow of people to other countries or states, which is mostly the result of the globalized world’s own supply and demand of labor, boosting them to leave their countries. It also comes from each country’s regions asymmetric development process, when the displacement is carried out inside it. Encouraged by the search for better opportunities, these workers face a variety of difficulties, which make them easy targets and available to illegal organizations that operate in smuggling of migrants, culminating in the reduction of these victims to the condition analogous to slavery. In order to combat this type of treatment, it is necessary to implement public politics, as well as the international standards that protect the migrant workers’ human rights effective compliance. The new Migration Law (13.445/2017), is also an important element in overcoming these individuals’ vulnerability, since it has brought a great regarding advance to migratory issue in Brazil. It becomes evident the need to enter in its confronting mechanisms of the victims’ vulnerability subjected to slave-like practices through these workers’ human rights realization, which constitute the guarantee of their freedom. In this sense, stands out, in this dissertation, ways to reach these rights effectiveness, through the right to development application, which prospect values of fraternity and humanization in society. Therefore, it is emphasized the forms of more humane treatment promoting to the individual, in order to guarantee their role in society as a subject of law and guarantees, aiming at the fundamental right to decent work full effectiveness. It is from this perspective that demonstrate the relevance of the right to development, bringing directions for the effective migration policies establishment, so that migrant workers have opportunities to make their choices freely to live a decent life. In this way, it will be possible to glimpse the suppression of the contemporary slavery.